Private Sector Training and Graduate Earnings - Booth, Alison L. (The Review of Economics and Statistics, 1993)
This paper uses a survey of British graduates to estimate the impact of employer-provided training on the earnings of men and women graduates. The results indicate that, although the training impact is reduced after controlling for endogeneity, some forms of training have a considerable impact. However, there are substantial gender differences in the earnings impact of various typ es of training. Moreover, men graduates are more likely to receive training than otherwise identical women. Copyright 1993 by MIT Press.